Considerations before orthodontic camouflage treatment in skeletal class III malocclusion - Marcella Budhiawan; Haru Setyo Anggani (Padjadjaran Journal of Dentistry, 2008)
Skeletal Class III malocclusions are caused by maxillary deficiency, mandibular protrusion, or a combination of the two. This patient, in this case, may have a sunken in face, strong chin appearance. Most persons with Class III malocclusions, which is a dentofacial deformity, show combinations of skeletal and dentoalveolar components. Orthodontic therapy is usually aimed at compensating for the underlying mild-moderate skeletal Class III discrepancy and patients with severe skeletal Class III discrepancies require a combination of orthodontic treatment and orthognathic surgery to correct the underlying skeletal pattern. By considering many factors, the orthodontic treatment can be done on mild to severe skeletal Class III. These factors are facial profile, dental relationship and skeletal pattern. Those factors should be considered a starting point in making a treatment decision. They give the limitation of orthodontic treatment in terms of whether the occlusion could be corrected, or whether the deformity could be camouflage.